Reabilitação do assoalho pélvico em pacientes com incontinência urinária pós prostatectomia radical - Andrade, Carla Elaine Laurienzo da Cunha [UNESP] (2014)
Objective: To evaluate impact of rectal electrical stimulation in urinary continence and sexual function rehabilitation in patients undergone to radical prostatectomy. Methods: This randomized controlled clinical trial included patients in preoperative workup for radical prostatectomy. Were evaluated quality of life (ICIQ-SF), erectile function (IIEF-5), urinary symptoms (IPSS score), urinary loss (Pad Test 1 hour), and pelvic floor muscular strenght (Perineometry), in four moments: preoperative, postoperative follow-up of 1, 3 and 6 months. Patients were randomized in three groups (control, verbal guidance and electrical stimulation). The verbal guidance group were instructed by a physiotherapist to practice exercises to empowering pelvic floor after catheter removal. The electrical stimulation group undergone to 14 sesions of pelvic floor electrical stimulation, with 35Hz frequency, twice a week. Results: Between October 2010 and September 2013, were included 123 patients undergone to radical prostatectomy with mild, moderate or high urinary incontinence (Pad Test ≥ 3 gr). These patients were randomized: control group (n:40), verbal guidance (n:41) and electrical stimulation (n:42). Demographics and pathological variables were similar between the groups. The analysis of the variables QoL, urinary symptoms, erectile function and perineometry did not demonstrate differences between the groups analysed. The Pad Test values in 6 months follow-up had no statistical significance between the groups (median were: 1,0gr (0-23,0); 1,0gr (0-78,0) and 1,0gr (0-18,0), respectively. Conclusion: QoL, urinary symptoms, erectile function and muscular strength do not show a better rehabilitation in electrical stimulation group in our study population. Pelvic floor electrical stimulation did not show impact in urinary continence after radical prostatectomy